Coordinative Two-Stage Superheated Steam Temperature Linkage Control Based on Multivariable Generalized Predictive Control Algorithm - Sheng TONG; Le LIU; Pengfei WANG (Zhongguo dianli)
In addition to their own characteristics such as long duration of time delay and large inertia, the controlled objects of superheated steam temperature in large thermal power generating units are affected by a considerable number of factors and model variations under different loading conditions. Especially with complicate coal quality or under volatile environment, the effect of superheated steam temperature control turns out to be very limited, which are based on traditional PID control and single variable generalized predictive control. In this paper, the models of superheated steam temperature system under three typical working conditions are established by virtue of recursive least square method, and then an optimization strategy of two-stage superheated steam temperature linkage control based on multivariable generalized predictive control (MGPC) is constructed. Meanwhile, the strategy is applied to the 330 MW subcritical units in a power plant. The practice results show that the optimal control strategy is effective to control the outlet steam temperature of superheater whenever the system is operated under stable loads or complicated variable loads.